EMPIRICAL CALIBRATION OF OXYGEN ISOTOPE FRACTIONATION IN ZIRCON - Valley J.W.; Bindeman I.N.; Peck W.H. (My University, 2003)
New empirical calibrations for the fractionation of oxygen isotopes among zircon, almandine-rich garnet, titanite, and quartz are combined with experimental values for quartz-grossular. The resulting A-coefficients (‰K 2) are: for the relation 1000 ln Y-X A Y-X (10 6 /T 2). The fractionation of oxygen isotopes between zircon and coexisting minerals can provide otherwise unavailable evidence of magmatic processes, including crystalli-zation, remelting, and assimilation-fractional crystallization.
Keywords: Zircon